Amelie : she'll change yuor life. - Tautou,Audrey Kassovitz,Mathieu
Amelie is looking for love,and perhaps for the meaning of life in general.We see her grow up in an original if slightly dysfunctional family.Now a waitress in central paris,she interacts curiously with her neighbors and customers,as well as a mysterious photomaton-image collector and one of his even more mysterious photo subjects.little by little,Amelie realizes that the way to happiness requires here to take her own initiatives and reach out to others.